Efektivitas Konseling Kelompok dengan Teknik Modelling Simbolik dalam Upaya Mengatasi Stigma Negatif Masyarakat Terhadap Mantan Pecandu Narkoba - Hermawanti, Riza Syahsia; Kusnadi, Kusnadi; Marianti, Lena (Journal of Society Counseling, 2023)
This research is about "The Effectiveness of Group Counseling Using Symbolic Modeling Techniques in Efforts to Overcome Society's Negative Stigma Against Former Drug Addicts". This research is motivated by information and globalization, various information can be obtained easily. One of the events currently being discussed among the public is the problem of negative stigma. This research aims to first, find out the negative stigma of society before conducting group counseling using symbolic modeling techniques in an effort to overcome the negative stigma towards former drug addicts. Second, to determine the effectiveness of group counseling using symbolic modeling techniques in an effort to overcome society's negative stigma towards former drug addicts. This research uses a descriptive quantitative approach, with a population of 67 people with a sample of 12 people using purposive sampling. Data collection techniques use observation, questionnaires, documentation. Data analysis techniques through the Wilxocon test with the help of the Windows SPSS version.26 program. The results of the research show first, the level of negative societal stigma towards former drug addicts before group counseling using symbolic modeling techniques was in the high category. Second, the results obtained show that Asymp.sig (2-tailed) is worth .002. With a value of .002<0.05, it can be concluded that Ha is accepted and H0 is rejected, meaning that group counseling using the Symbolic Modeling technique is effectively used to reduce society's negative stigma towards former drug addicts.